Batman begins [videorecording (DVD)] - Nolan, Christopher, 1970-; Bale, Christian, 1974-; Caine, Michael; Neeson, Liam; Holmes, Katie, 1978-; Oldman, Gary; Kane, Bob (Warner Home Video, 2005)
As a boy a young Bruce Wayne watched in horror as his millionaire parents were slain in front of his eyes. This trauma led him to become obsessed with revenge. After disappearing to the East where he seeks counsel with a ninja cult leader, he returns to his now decaying Gotham City. The City is now overrun by organized crime and dangerous individuals manipulating the system. The discovery of a cave under his mansion, and a prototype armoured suit leads him to take on a new persona. He becomes Batman and strikes fear into the hearts of men who do wrong. With the help of rising cop Jim Gordon, Batman sets out to take down the various criminal schemes that have been set in motion by individuals such as mafia don Falcone, the twisted doctor/drug dealer Jonathan 'The Scarecrow' Crane, and a mysterious third party that is quite familiar with Wayne and waiting to strike when the time is right.